Organisational, Professional, and Interprofessional Communication in the Protection and Promotion of Children’s Rights - Garayová, Lilla (Interdisciplinary and Child-Friendly Communication, 2025)
This chapter explores the critical role of communication in advancing the rights and well-being of children, particularly within legal, organisational, and interdisciplinary contexts. Clear and purposeful communication provides a basis for effective cooperation among professionals such as social workers, psychologists, educators, medical practitioners, and legal experts, so that their decisions are informed by and responsive to the child’s overall needs. The chapter examines the key aspects of communication, including organisational communication within legal institutions, interprofessional collaboration, and child-sensitive practices, while addressing common challenges such as power dynamics, differing terminologies, and lack of standardised protocols. The study also identifies key tools and techniques based on best practices and case studies, such as digital platforms, trauma-informed training, plain language initiatives, and multidisciplinary teams, that enhance the efficiency and responsiveness of child centred systems.Keywords: children’s rights, communication in law, interdisciplinary collaboration, child-friendly justice, organisational communication, legal professionals, trauma-informed practices, plain language initiatives, multidisciplinary teams, child-sensitive practices, best interests of the child